Analysis of marketing strategies to increase broiler chicken sales at chicken room broiler farm, South Lampung - Akbar, Wahyu Esa; Purnomo, Agus (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to analyze effective marketing strategies to increase broiler chicken sales in South Lampung, Indonesia, amid the growing competition in the market. The rapid growth of broiler chicken farms has raised consumer awareness of the importance of animal protein, but the increasing number of farms has intensified market rivalry. Traditional marketing methods, still dominant in the industry, are considered less effective in utilizing modern technology to reach a broader audience. A qualitative method was employed in this study, involving observation and interviews at the Chicken Room Broiler Farm in South Lampung. Data were gathered to assess the effectiveness of various marketing strategies implemented by the farm. The analysis highlights the success of social media-based marketing strategies, particularly through Instagram and Facebook, in expanding the market and enhancing customer loyalty. The farm's consistent product quality and excellent customer service were also identified as key strengths contributing to its competitive edge. Despite these strengths, several challenges were identified, including price fluctuations, disease outbreaks, and inadequate infrastructure, which hinder the farm's potential growth. A SWOT analysis revealed the need for innovative strategies that leverage internal strengths and external opportunities while addressing weaknesses and threats. In conclusion, the study emphasizes the importance of adopting modern marketing techniques, such as social media marketing, to stay competitive in a rapidly growing and competitive industry. Addressing infrastructural limitations and managing external threats are also critical for sustained success.